Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Minat Beli Konsumen Es Teh Poci - Sofiah , Shella; Nurmulya, Fitrasyah (JURNAL MANAJEMEN BISNIS TRI BHAKTI, 2024)
Buying interest in Dukuh Zamrud Poci Ice Tea can be influenced by promotions and good service quality, where good promotions can influence consumers' buying interest. As for good service quality, it will affect promotions, so that consumer buying interest increases. The purpose of this study was to identify, explain and analyze the effect of promotion and service quality on consumer buying interest in Dukuh Zamrud Poci Ice Tea. The sampling technique used in this research is purposive sampling technique. Samples taken as many as 100 customers. The analysis used in this study is multiple regression analysis along with the classical assumption test. The results of this study prove that there is a positive and significant influence between promotions on consumer buying interest, as well as a positive and significant influence between service quality and consumer buying interest at Dukuh Zamrud Poci Es Tea. In this study, it states that there is a partial effect of promotion on consumer buying interest. The results of the coefficient of determination show that the R Square result is 0.684 which means that Promotion and Service Quality contribute 68.4% in influencing Consumer Purchase Interest in Dukuh Zamrud Es Tea Poci, and the remaining 31.6% is influenced by other variables outside this research.